2011
DOI: 10.1128/jb.00452-11
|View full text |Cite
|
Sign up to set email alerts
|

RNase III-Dependent Expression of the rpsO-pnp Operon of Streptomyces coelicolor

Abstract: We have examined the expression of the rpsO-pnp operon in an RNase III (rnc) mutant of Streptomyces coelicolor. Western blotting demonstrated that polynucleotide phosphorylase (PNPase) levels increased in the rnc mutant, JSE1880, compared with the parental strain, M145, and this observation was confirmed by polymerization assays. It was observed that rpsO-pnp mRNA levels increased in the rnc mutant by 1.6-to 4-fold compared with M145. This increase was observed in exponential, transition, and stationary phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Quantification of the band intensities indicated that the JSE1880 mRNA preparation (lane 5) contained ca. 2.5 times as much of the readthrough transcript as the M145 preparation (lane 2), a value consistent with the levels observed in Northern blots of RNAs from M145 and JSE1880 (15). Figure 1 also shows that the JSE1880 mRNA preparation contained transcripts of the ramR gene (lane 8), which encodes a response regulator (35).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Quantification of the band intensities indicated that the JSE1880 mRNA preparation (lane 5) contained ca. 2.5 times as much of the readthrough transcript as the M145 preparation (lane 2), a value consistent with the levels observed in Northern blots of RNAs from M145 and JSE1880 (15). Figure 1 also shows that the JSE1880 mRNA preparation contained transcripts of the ramR gene (lane 8), which encodes a response regulator (35).…”
Section: Resultssupporting
confidence: 62%
“…2 and compared those results with previous data obtained for these two transcripts by Northern blotting. Our Northern blotting studies indicated a 1.6-fold increase in the rpsO transcript level, encoding ribosomal protein S15, in the mRNA pools from JSE1880 compared to that of M145 during exponential growth (15). The corresponding ratio obtained from the RNA-Seq data was ca.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Overexpression of PNPase led to decreased antibiotic production in Streptomyces antibioticus (155). Since the expression of pnp is RNase III dependent in S. coelicolor (156), it will be interesting to investigate the connection of PNPase, RNase III, and antibiotic production. Little is known about the functions of other RNases in Streptomyces.…”
Section: Rna Regulation Of Antibiotic Productionmentioning
confidence: 99%
“…1B). This substrate, derived from the S. coelicolor rpsO-pnp operon, contains the rpsO terminator and the intergenic hairpin that is the substrate for RNase III (18). Figure 3A shows a typical polyacrylamide gel separation of the products of RP3 phosphorolysis using wild-type PNPase.…”
Section: Rationale For the Construction Of The Pnpase Mutantsmentioning
confidence: 99%